2010
DOI: 10.1002/art.27720
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of complement by cartilage oligomeric matrix protein allows for a novel molecular diagnostic principle in rheumatoid arthritis

Abstract: Objective Cartilage oligomeric matrix protein (COMP) is a structural component of cartilage where it catalyzes collagen fibrillogenesis. Elevated amounts of COMP are found in serum during increased turnover of cartilage associated with active joint diseases, such as rheumatoid arthritis (RA) and osteoarthritis (OA). In this study we investigated the ability of COMP to regulate complement. Such capacity was previously shown for some cartilage proteins. Methods Regulation of complement by COMP was studied usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
109
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 38 publications
(34 reference statements)
4
109
0
1
Order By: Relevance
“…Elevated levels of COMP in serum or synovial fluid correlate with autoimmune or joint inflammatory diseases, such as rheumatoid arthritis, osteoarthritis, and systemic sclerosis (26)(27)(28). We showed that COMP also functions as a regulator of complement activity (22). COMP binds C1q and mannose-binding lectin to block the classical and lectin complement pathways, respectively.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Elevated levels of COMP in serum or synovial fluid correlate with autoimmune or joint inflammatory diseases, such as rheumatoid arthritis, osteoarthritis, and systemic sclerosis (26)(27)(28). We showed that COMP also functions as a regulator of complement activity (22). COMP binds C1q and mannose-binding lectin to block the classical and lectin complement pathways, respectively.…”
mentioning
confidence: 87%
“…The pentameric COMP is assembled through interchain disulfide bonds, and each monomer consists of an N-terminal cysteine-rich domain used for oligomerization. It contains four epidermal growth factor (EGF) domains, eight thrombospondin type 3 repeats, and a C-terminal globular domain (22). The primary function of COMP is to catalyze collagen fibrillogenesis and to stabilize ECM (23,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has been proposed to contribute to the local pro-inflammatory milieu in joints of patients suffering from RA. C1q, the initiator of the classical pathway, binds to decorin [5,6], biglycan [5], fibronectin [7], laminin [8], osteoadherin [6], fibromodulin [9], cartilage oligomeric matrix protein (COMP) [10] and more weakly to lumican [6] and chondroadherin [6]. These interactions can result in inhibition of C1q (decorin, biglycan, COMP) or in activation of the classical pathway (fibromodulin, osteoadherin).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, those extracellular matrix (ECM) molecules that activate C1q and the ensuing complement cascade also bind complement inhibitors such as factor H (FH) [6] and C4b-binding protein (C4BP) [11] in order to limit inflammation. Furthermore, COMP, an established marker of joint destruction, activates the alternative complement pathway [10,12].…”
Section: Introductionmentioning
confidence: 99%